A Naturalistic Examination of the Acute Effects of High‐Potency Cannabis on Emotion Regulation Among Young Adults: A Pilot Study - Cavalli, Jessica M.; Cuttler, Carrie; Cservenka, Anita (Human psychopharmacology, 2025)
ABSTRACT Objective Despite the popular public perception that cannabis use may be beneficial for relieving mental health symptoms, the empirical evidence remains equivocal. Various legal hurdles limit the ability to research whether acute high‐potency cannabis use affects mental health‐related processes. Therefore, the current study used a novel methodology to examine the acute effects of high‐potency cannabis flower on emotion regulation. Methods Using a remote, within‐subjects study design, 12 young adult (ages 21–30) cannabis users (who used cannabis at least 1 day/week on average across the past year) completed measures of emotion regulation while sober and acutely intoxicated in a counterbalanced manner. Participants completed the Emotional Go/No‐Go Task to measure implicit emotion regulation and a cognitive reappraisal task to assess explicit emotion regulation. For the intoxication condition, participants were observed smoking cannabis flower in their homes via videoconferencing. Results Participants reported a more positive mood and decreases in anxiety while intoxicated. There was no evidence that acute high‐potency cannabis affected participants' implicit or explicit emotion regulation task performance. Conclusions Future research with larger samples might consider adopting this novel remote study design to assess the acute effects of high‐potency cannabis use on different measures of emotion regulation and other health outcomes.